Principles and Practices to Secure and Hold Interest - R. Kirby Barrick; Andrew C. Thoron (EDIS)
Securing and holding student interest is a major challenge for teachers. Once the curriculum is set, then teachers must decide how to teach the content, particularly how to build lasting interest in the content being taught. Students learn more and retain what they have learned longer when they are interested in the content, see its usefulness, and are motivated to learn and apply what they have learned. This 3-page fact sheet discusses what makes a topic or lecture interesting for students and ways to improve teaching methods to keep students engaged and interested in the subject matter. Written by R. Kirby Barrick and Andrew C. Thoron, and published by the Agricultural Education and Communication Department., January 2016.